(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study was a qualitative research study utilizing the phenomenological research design, which was carried out to ascertain the lived experiences of teachers on the effectiveness of alternative strategies to corporal punishment in Ghanaian Basic schools. With the in-depth interview of fifteen teachers and focus group discussion with fifteen headteachers in Mampong Municipality, three main benefits were identified from the use of these strategies namely: improved pupil-teacher relationships, improved behavior, and improved school climate. This implies that the teachers perceive the alternative strategies as effective to some extent. It was recommended that to encourage the use of these strategies in Ghanaian basic schools, there should be continuous education of stakeholders on the use and the benefits of the use of these alternative strategies.